Spigot in pneumothorax cavity: A rare complication of endobronchial Watanabe spigot - Shion Miyoshi; Kyohei Kaburaki; Hajime Otsuka; Kazuma Kishi (Respirology Case Reports, 2021)
Key message Spigot dropping is a rare but an intractable complication, because it is difficult to salvage a dropped spigot from the thoracic cavity. If the pneumothorax with a large fistula is recurrent, replacement with a larger size spigot may be recommended.